BSDEs driven by normal martingale. Issue 4 (4th March 2022) - El Otmani, M.; Marzougue, M.
Abstract : The aim of this paper is to study backward stochastic differential equation driven by a class of normal martingale. We prove the existence and uniqueness results of the solution under the stochastic Lipschitz condition by mean the martingale representation theorem. In addition, we show that the solution of these equations provides a viscosity solution of the associated system with partial differential equations.